Descriptive Study of Acute Poisoning Cases Admitted to Yalgado Ouédraogo University Hospital in Ouagadougou, Burkina Faso - Traore, Salimata; Issa Somé, Touridomon; Lamien Sanou, Assita; Yakoro, Alphonse; Innocent Guissou, Pierre (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: To analyze the features of the acute poisoning cases admitted to Yalgado Ouédraogo University Hospital (CHU) in Ouagadougou. Methods: It is a prospective study conducted in 2014. All the poisoning cases admitted to the Medical and Paediatric Emergency services in Yalgado Ouédraogo University Hospital (CHU) in Ouagadougou since January to December 2014 were included in this study. The clinical records of poisoned patients were analysed. The data collection was done through a questionnaire. Results: Acute poisoning comprised 672(5%) out of 13442 of all the admissions to the Medical and Paediatric Emergency services in Yalgado Ouédraogo University Hospital (CHU) in Ouagadougou. About 47% of the poisoned were children up to 16 years old. Also, 55% of the poisoned were female. Medicines were the major responsible factor (41%) and then household products (27%). The poisonings were mainly (70%) accidental and unintentional; and the remaining were intentional (suicide attempt). The study tools were clinical diagnosis, history taking, and physical examination. The outcomes were positive in 70% of the cases; but negative and resulting in death in 3% of cases. About 7% of those poisoned ran away during their hospitalisation and 20% were transferred to other wards for the rest of their treatment. Conclusion: The study provided an inventory of the situation regarding acute poisoning in the emergency services of Yalgado Ouédraogo University Hospital in Ouagadougou.